Implementation of Harris Hawks optimization for load frequency control of hydropower plant - Devendra Potnuru; Lagudu Venkata Suresh Kumar; Bankuru Sonia; Yellapragada Venkata Pavan Kumar; Darsy John Pradeep; Challa Pradeep Reddy (Institute of Advanced Engineering and Science, 2022)
Hydropower has been used for many years and is essential to meet the renewable energy ambition of the world at present. In a hydroelectric power plant, voltage and frequency control are required, but, the voltage control could be done on the load side. In the present paper, frequency control using Harris Hawks optimization (HHO) for improved performance has been presented. Simulations are performed on the dynamic model of the hydropower plant and results are compared with the conventional PID that is designed using the Ziegler-Nichols method. The efficacy of the proposed algorithm is also tested at dynamic conditions of the hydropower plant.